1993
DOI: 10.1161/01.atv.13.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet properties of protein S-nitrosothiols derived from nitric oxide and endothelium-derived relaxing factor.

Abstract: 5-Nitrosothiols may serve as carriers in the mechanism of action of endothelium-derived relaxing factor (EDRF) by stabilizing the labile nitric oxide (NO) radical from inactivation by reactive species in the physiological milieu and by delivering NO to the heme activator site of guanylyl cyclase. Low-molecularweight thiols, such as cysteine and glutathione, form 5-nitrosothiol adducts with vasodilatory and antiplatelet properties, and protein thiols can interact in the presence of NO and/or EDRF to form unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(68 citation statements)
references
References 41 publications
2
65
0
1
Order By: Relevance
“…There have been several reports on RSNO-dependent inhibition of blood clot formation (18) and platelet aggregation (20)(21)(22)(23). In all of these cases, the mechanism of inhibition has been attributed to either the NO-mimicking activity of RSNOs in triggering the NO͞cGMP pathway or has involved the transnitrosation or S-thiolation of an essential free thiol(s) on the proteins participating in thrombosis or platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on RSNO-dependent inhibition of blood clot formation (18) and platelet aggregation (20)(21)(22)(23). In all of these cases, the mechanism of inhibition has been attributed to either the NO-mimicking activity of RSNOs in triggering the NO͞cGMP pathway or has involved the transnitrosation or S-thiolation of an essential free thiol(s) on the proteins participating in thrombosis or platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…S-Nitrosothiols (RSNO) can elicit many of the various physiological regulatory functions attributed to nitric oxide/endothelium-derived relaxing factor, including smooth muscle relaxation [l-4], platelet deactivation [5,6], immunosupression [7] and neurotransmission [8]. RSNO occur in human venous plasma mainly as S-nitroso-albumin (7 PM) [9], and 0.3 ,uM GSNO has been measured in human bronchial lavage fluid [lo].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a discrepancy between the metabolism phenomenon, and subsequent signalling events. It has been documented that NO delivery into cells from protein RSNO molecules, such as albSNO, requires a prior transfer of NO to a low molecular weight thiol, via transnitrosation [8,9]. Our experiments were performed in the absence of added thiol and this may explain why metabolism of albSNO was not accompanied by cGMP accumulation or inhibition of platelet aggregation.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have reported delivery of NO into cells via transnitrosation reactions, which involve transfer of NO + from one thiol to another [5][6][7]. For protein RSNOs (such as Snitrosoalbumin) to mediate platelet inhibition, prior exchange of NO onto a low molecular weight thiol appears necessary [8,9]. Free thiols are available on the platelet surface itself [10,11] and S-nitrosation of these thiols may be a further possible pathway of anti-platelet action.…”
Section: Introductionmentioning
confidence: 99%